Noxious Neighbours? Interrogating the Impacts of Sex Premises in Residential Areas. (January 2013) - Hubbard, Phil; Boydell, Spike; Crofts, Penny; Prior, Jason; Searle, Glen
Premises associated with commercial sex—including brothels, striptease clubs, sex cinemas, and sex shops—have increasingly been accepted as legitimate land uses, albeit ones whose location needs to be controlled because of assumed 'negative externalities'. However, the planning and licensing regulations excluding such premises from areas of residential land use are often predicated on assumptions of nuisance that have not been empirically substantiated. Accordingly, this paper reports on a survey of those living close to sex industry premises in New South Wales, Australia. The results suggest that although some residents have strong moral objections to sex premises, in general residents note few negative impacts on local amenity or quality of life, with distance from a premise being a poor predictor of residents' experiences of nuisance. These findings are considered in relation to the literatures on sexuality and space given regulation which ultimately appears to reproduce heteronormative moralities rather than respond to genuine environmental nuisances.